KENDALA GURU DALAM PROSES BELAJAR MENGAJAR SELAMA MASA COVID-19 DI WILAYAH PEDESAAN - Sunarto Sunarto; Abu Dzar Al Ghifari (Jurnal Pendidikan Ilmu Sosial, 2021)
This study aims to determine the various obstacles experienced by teachers in the learning process during the spread of the coronavirus. This research was conducted at SMP Negeri 7 Budong-budong, because the position of this school is far from the center of Central Mamuju Regency. To obtain more detailed information about the research topic, this research was conducted using a qualitative approach with a case study method. There are several techniques used in collecting data in this research, namely observation, indepth interviews, and documentation studies. At the interview stage, the researcher collected information from 3 teachers who were considered capable of providing valid data according to the research topic. After the data is collected, then the data is analyzed using the data analysis method of the Miles and Hubermen model which includes data reduction, data presentation and the process of drawing conclusions. From the results of the study, it was found that several obstacles were faced by teachers in the teaching and learning process during the covid-19 pandemic, namely: 50% due to the lack of infrastructure (for example smartphones, computers, internet networks, etc.), 15% due to lack of support from people. parents or guardians, geographical conditions that sometimes make it difficult for teachers to get to school as much as 15%, 10% because of the ability of students who are still lacking in understanding learning and 10% due to boredom experienced by students during the covid -19 periods. In addition, to adjust the teaching and learning process during the pandemic, teachers at SMP Negeri 7 Budong-budong carried out several learning methods such as group system learning, online learning, and learning using modules.